Report on China's Cruise Industry (Springer Singapore, 2018)
The book contains 12 contributions that explain the current state of China's cruise industry and future development. Dating from the 1960s and with the rapid development of over 50 years, the modern cruise industry has developed into one of the fastest growing industries with the most remarkable economic benefits in the global tourism and hospitality industry, known as a "golden industry on the golden waterway". In recent years, with the gradual saturation of international cruise market and the eastward-moving trend of the center of cruise market, China has become a strategic emerging market with which international cruise lines have been competing. A number of international cruise lines, including Costa Crociere, Royal Caribbean Cruises, Princess Cruises, MSC Cruises, Star Cruises, Norwegian Cruise Line and Dream Cruises, have entered the cruise market in Mainland China. .